Localized Corrosion: Passive Film Breakdown vs. Pit Growth Stability: Part IV. The Role of Salt Film in Pit Growth: A Mathematical Framework. Issue 6 (19th March 2019) - Li, Tianshu; Scully, J. R.; Frankel, G. S.
Abstract : In Part II of this series, a framework for pit stability established, and it was expanded in Part III to describe salt film formation in pits. It was shown that a salt film was not required for pit stabilization; it is just a consequence of a pit achieving diffusion-controlled growth. A salt film can form on the surface of both metastable and stable pits when the maximum pit dissolution current density, i diss, max, exceeds the diffusion-limited current density, i lim . Based on this clarifying framework, this paper shows mathematically that the main function of a salt film is to adjust the actual potential at pit surface by regulating its thickness, thus to restrict the anodic dissolution rate of pit surface metal at the value of diffusion-limited current density. As a result, the film thickness will respond to any changes in the applied potential, temperature, pit depth, ohmic potential drop in the solution and perforation radius of the pit cover. Additionally, the pit stability criteria that have been discussed previously in the literature are reinterpreted using the new framework, and they are unified by the critical temperatures, potentials and pit depths for pit stabilization and salt film formation proposed in Part III.